Clinical significance of internal carotid artery restenosis following carotid endarterectomy - Radak Đorđe; Tanasković Slobodan; Babić Srđan; Aleksić Nikola (Srpski Arhiv za Celokupno Lekarstvo, 2012)
Carotid endarterectomy has been established as the preferred treatment for symptomatic and asymptomatic high-grade carotid stenosis. Internal carotid artery restenosis is defined as a specific entity with a great clinical significance in carotid surgery due to accompanied increased future cerebral ischemic events risk. Carotid restenosis is the result of neointimal hyperplasia in the early postoperative period (within 36 months) or recurrent atherosclerotic lesions at a later date. While the restenotic lesions caused by neointimal hyperplasia are determined by ultrasound as smooth lesions, atherosclerotic carotid stenosis has almost the same ultrasound and angiographic characteristics as primary atherosclerotic lesions. Some authors believe that patients with internal carotid artery restenosis have insignificant risk of stroke or progression to total occlusion, and suggest conservative treatment only. On the other hand, many surgeons have more aggressive attitude towards the treatment of asymptomatic carotid stenosis and indicate surgical treatment in asymptomatic patients with carotid restenosis above 80%. The aim of our paper was to present a review of literature available data concerning etiology, pathophysiology, clinical significance and treatment of carotid restenosis following endarterectomy. Numerous studies have reported satisfactory results of redo endarterectomy and carotid angioplasty as treatment options of carotid restenosis. Carotid angioplasty for primary atherosclerotic lesions treatment is accompanied by a high carotid restenosis rate and therefore its role in primary carotid symptomatic and asymptomatic stenosis treatment is still the issue of numerous debates and the subject of extensive ongoing clinical studies worldwide.